Secular trends of body mass index in North Indian children with Type 1 diabetes do not support the Accelerator Hypothesis. (2nd October 2015) - Dayal, Devi; Samprathi, Madhusudan; Jayaraman, Dhaarani; Kohat, Dilesh; Bhalla, Anil Kumar
Summary: Objective: The accelerator hypothesis, which proposes a link between Type 1 diabetes (T1D) and Type 2 diabetes (T2D) through weight‐related insulin resistance, remains untested in developing countries with increasing rates of childhood obesity and T1D, and different ethnicities. We aimed to test the accelerator hypothesis in the context of a significant increase in T1D at our centre. Design and methods: Medical records of children diagnosed with T1D between January 2005 and December 2014 were retrospectively reviewed. The body mass index (BMI) standard deviation scores (SDSs) were calculated using height and weight measurements recorded 1–2 months after diagnosis of T1D and compared with age‐matched anthropometric data. The rate of change in BMI SDSs over time was calculated. Analysis of BMI data was undertaken for the three age categories: <5, 5 to <10 and >10 years. Results: The mean age at diagnosis of 467 children with T1D was 7·27 ± 0·32 years and showed no change over the study period. There was a yearly increase of 14·11% in patient numbers; this increase was similar in the three age categories (22·7%, 17·0%, 16·3%, respectively, P = 1·0). Comparison of patient numbers between the two time periods of 5 years each showed a marked increase during 2010–2014 (148 vs 319, % increase 115·5%). The mean BMI SDSs at diagnosis in the three age categories were similar ( P = 1·0) and showed a yearly change of −0·36; the mean change in the three age categories was also similar (−0·35, −0·27, −0·46, respectively, P = 1·0). No correlation was found between age at diagnosis and BMI SDSs (correlation coefficient 0·010, P = 0·82). The mean BMI SDS in patients was significantly lower compared to controls (−0·54 vs −0·02, P = 0·001). Conclusion: There was no association between BMI SDS and age at diagnosis in children with new onset T1D. Further studies are needed to test whether the accelerator hypothesis is relevant in developing countries.